Chapter 32 Discourse Network Analysis - Eder, Franz (Taylor & Francis, 2023)
This chapter introduces Discourse Network Analysis (DNA). DNA argues that actors are communicative agents that discursively seek to promote their policy preferences in a contested domestic political arena, by building coalitions of like-minded. Thus, DNA bridges the gap between Foreign Policy Analysis (FPA) and public policy by integrating domestic politics into the analysis of foreign policy decision-making. DNA rests on two methodological approaches. First, it uses qualitative content analysis for gathering and coding the statements of actors. Second, it utilizes social network analysis to link statements and actors in networks, and thus makes discursive strategies and processes of coalition-building visible. To illustrate the applicability of DNA to FPA, this chapter discusses the debates in the British House of Commons on the Iraq War of 2003.